Image processing tools for the validation of CryoEM maps. (21st July 2022) - Sorzano, C. O. S.; Vilas, J. L.; Ramírez-Aportela, E.; Krieger, J.; del Hoyo, D.; Herreros, D.; Fernandez-Giménez, E.; Marchán, D.; Macías, J. R.; Sánchez, I.; del Caño, L.; Fonseca-Reyna, Y.; et al.
Abstract : A progressive CryoEM map validation scheme is presented. The scheme may include the map, half maps, 2D classes, particles, angles, coordinates, defoci, micrographs, and image processing workflow. Abstract : The number of maps deposited in public databases (Electron Microscopy Data Bank, EMDB) determined by cryo-electron microscopy has quickly grown in recent years. With this rapid growth, it is critical to guarantee their quality. So far, map validation has primarily focused on the agreement between maps and models. From the image processing perspective, the validation has been mostly restricted to using two half-maps and the measurement of their internal consistency. In this article, we suggest that map validation can be taken much further from the point of view of image processing if 2D classes, particles, angles, coordinates, defoci, and micrographs are also provided. We present a progressive validation scheme that qualifies a result validation status from 0 to 5 and offers three optional qualifiers (A, W, and O) that can be added. The simplest validation state is 0, while the most complete would be 5AWO. This scheme has been implemented in a website https://biocomp.cnb.csic.es/EMValidationService/ to which reconstructed maps and their ESI can be uploaded.